2011
DOI: 10.1111/j.1540-5826.2011.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Intensive Vocabulary Instruction for Students At Risk for Reading Disability

Abstract: Concerns regarding literacy levels in the United States are long standing. Debates have existed for decades regarding the most effective ways to teach reading, especially the polarizing dilemma of how much to focus on decoding versus code-emphasis and whole language instruction. Fortunately, as a result of concentrated research efforts and analyses of the extant literature on teaching reading, perhaps spurred by these debates, we know more now than we ever have about how to teach basic reading skills. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As a result, a person understands and uses words within his or her lexicon with varying degrees of precision (Baker, Simmons, & Kame’enui, 1998). Given the evolutionary nature of word learning, a judicious discussion of a strategy’s effectiveness for teaching vocabulary must evaluate its contribution to breadth and depth of word learning (Coyne, McCoach, Loftus, Zipoli, & Kapp, 2009; Pullen, Tuckwiller, Ashworth, Lovelace, & Cash, 2011) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a person understands and uses words within his or her lexicon with varying degrees of precision (Baker, Simmons, & Kame’enui, 1998). Given the evolutionary nature of word learning, a judicious discussion of a strategy’s effectiveness for teaching vocabulary must evaluate its contribution to breadth and depth of word learning (Coyne, McCoach, Loftus, Zipoli, & Kapp, 2009; Pullen, Tuckwiller, Ashworth, Lovelace, & Cash, 2011) .…”
Section: Discussionmentioning
confidence: 99%
“…Differences between receptive and expressive learning may be attributed to the learning demands inherent within expressive language. The expressive tasks, as used in the study, assessed a deeper level of word knowledge than did the receptive task (Coyne et al, 2009; Pullen et al, 2011). It is reasonable to assume that the brief, explicit format of the instruction was sufficient for establishing initial word meanings but was insufficient for promoting deeper levels of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, we conducted an ancestral search of all primary studies identified in the initial full-text screen, as well as of relevant syntheses that emerged from the initial search (Austin et al, 2017;Elbaum et al, 2000;Pullen et al, 2011;Scammacca et al, 2007;Torres, 2016;Wanzek et al, 2016). From the primary studies, we identified and screened 45 titles and abstracts.…”
Section: Literature Searchmentioning
confidence: 99%
“…Following storybook reading, students are provided with extended opportunities to gain a deeper understanding of the target words. IVI implementation during storybook reading has been described in detail by researchers Pullen, Tuckwiller, Ashworth, Lovelace, & Cash, 2011): (a) before reading, teacher prompts students to pronounce target words, (b) students are told to listen for each "magic word" and raise their hand when they hear one in the story, (c) words are acknowledged in the story and sentences that contained each word are reread, (d) students are given a simple, student-friendly definition, (e) the teacher rereads the sentence with the definition instead of the target word, and last, (f) students are prompted to again pronounce the word. Following this 10-20 minute storybook reading session, students are engaged in after-reading opportunities to interact with words in other rich and varied ways (Beck et al, 2002).…”
Section: Components Of Ivi Have Been Supported By Past Research and Rmentioning
confidence: 99%